Flaubert en Slovaquie : modèle ou mauvaise direction ? - Jana Truhlářová (Flaubert: Revue Critique et Génétique)
Flaubert has had a thorny path in Slovakia : from the initial rejection of his novel Madame Bovary and its evaluation as “misdirection” at the turn of the nineteenth and twentieth centuries, through its reception as a model of writing in the 1930s (Pavel Bujnák, Juraj Slávik); the direct inspiration of writers in the 1960s (Pavel Vilikovský, Dušan Kužel), to serene reflection with deep understanding (Jozef Felix, Anton Vantuch, Albín Bagin) and the sensitive approach of translators in the 1980s-1990s (Soňa Hollá, Ladislav Franek and others) – this is the story of Flaubert in Slovakia. The article attempts to shed light on this long and complex journey, focusing in particular on the critic of Flaubert criticism and the re-evaluation of misinterpretations and preconceptions of Flaubertian writing in Slovak literary research.